Desain Perangkat Pembelajaran Konsep Listrik Statis Dengan Strategi Berdiferensiasi Dalam memfasilitasi Pendidikan Inklusi - Julanita Saleh; Abdul Haris Odja; Masri Kudrat Umar; Mursalin Mursalin; Muhammad Yusuf; Trisnawaty Junus Buhungo; Muznawaty Pilobu (Postgraduate, University of Mataram, 2024)
Students' learning needs need to be considered when teaching in the classroom. Implementation of differentiated learning is one of the teaching applications that pays attention to students' needs. The study aims to design static electricity learning devices with a differentiated approach in facilitating inclusive education. The study is part of the development of learning devices consisting of three stages, namely: preliminary stage, development stage and implementation stage. The results show a valid value teaching module with an average value of 81.25 including the valid category. In the implementation, a trial of differentiated learning devices was carried out through teaching in class IX. At this stage, information was obtained on the value of the implementation of learning implementation above 90 including the Very High category. Likewise, student learning outcomes at this implementation stage increased with an N-Gain value of 0.578 including the moderate category. The effect size test value was obtained at 6,510 including a strong effect. This shows that the implementation of the differentiated learning device design has a strong effect on static electricity learning outcomes. The conclusions of the study were obtained as follows: (1) the design of differentiated learning devices assessed by experts and practices is valid; (2) the implementation of the differentiated learning device design is included in the high category, there are two students who have obstacles in the form of slow learners at the regular school which is the trial location; (3) the design of the differentiated learning device which is arranged effectively is shown by the N-Gain value in the medium category and the effect size value in the strong effect category